The dynamics of attached and free-living bacterial population in tropical coastal waters - Lee, S.W.; Lee, C.W.; Bong, C.W.; Narayanan, Kulathuramaiyer; Sim, E.U.-H. (CSIRO, 2015)
We investigated the dynamics of attached and free-living bacterial abundance over a period of 18 months in tropical coastal waters of Malaysia. We measured the abundance at both oligotrophic coastal water (Port Dickson) and eutrophic estuary (Klang), and hypothesised that attached bacteria are predominant in eutrophic waters. We found that bacterial abundance was higher at Klang than Port Dickson (Student's t-test: t≤4.87, d.f.≤19, P<0.001). Attached bacteria also formed a large fraction of the total bacteria at Klang (75% ±13s.d.) relative to Port Dickson (56% ±22), and showed preference for chlorophyll-a-based particles rather than total suspended solids. The bacterial community structure was clearly different between the two stations but was similar between the attached and free-living bacterial population. Our results showed the importance of attached bacteria in eutrophic water where they could play a major role in carbon and nutrient cycling.